2017
DOI: 10.1002/anie.201609409
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Restructuring Mutations Can Reverse the Thermodynamic Signature of Ligand Binding to Human Carbonic Anhydrase

Abstract: This study uses mutants of human carbonic anhydrase (HCAII) to examine how changes in the organization of water within a binding pocket can alter the thermodynamics of protein–ligand association. Results from calorimetric, crystallographic, and theoretical analyses suggest that most mutations strengthen networks of water‐mediated hydrogen bonds and reduce binding affinity by increasing the enthalpic cost and, to a lesser extent, the entropic benefit of rearranging those networks during binding. The organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…The water molecules are highly important and poorly understood participants in protein-ligand association ( Klebe, 2015 ; Fox et al, 2017 ). However, there are a number of difficulties and uncertainties in the analysis of water molecules in active sites of crystal structures.…”
Section: Discussionmentioning
confidence: 99%
“…The water molecules are highly important and poorly understood participants in protein-ligand association ( Klebe, 2015 ; Fox et al, 2017 ). However, there are a number of difficulties and uncertainties in the analysis of water molecules in active sites of crystal structures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that Ser26 does not govern ligand selectivity through sidechain H bond interactions, since a fully transport-active AdiC S26A mutant shows a normal capacity to distinguish Arg + from Arg +2 11 , 30 . However experimental and theoretical studies, however, have shown that water molecules can, in some cases, take over the role of the mutated residue within the binding pocket 31 , 32 . One can therefore not totally rule out the possibility that the Ser26 sidechain or a replacing bound water molecule might act in a local mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…When a substrate binds to the active site of cytochrome P450 monooxygenase, for example, different orientations often yield different products (115). Studies of H/S compensation suggest that different poses of bound ligand often have different enthalpic and entropic signatures, but similar free energies of binding (16,17,36,56). An understanding of the link between the orientation of a bound substrate and its thermodynamic profile could, thus, enable better methods to change-or, at least, detect-that orientation in efforts to design biocatalysts.…”
Section: The Protein the Contribution Of Protein Dynamics-and Associmentioning
confidence: 99%
“…Stabilization was apparent in an increase in the number of crystallographically observed fixed waters, an increase in the number of water-water hydrogen bonds (i.e., the number of pairs of crystallographically observed fixed waters separated by a distance of 3.5 Å or less), a decrease in the length of water-water hydrogen bonds, and/or a decrease in the B-factors of fixed waters; destabilization correlated with the opposite effects.Interestingly, the ligand with the greatest binding affinity was not the one that buried the largest amount of nonpolar surface area-a result that might be predicted by a classical description of the hydrophobic effect-but, rather, the one that yielded a particularly stable (and enthalpically favorable) hydration pattern around the protein-ligand complex.Incremental variations in the structure of a binding pocket. Taking an approach complementary to that of Klebe, we used mutants of HCAII to determine how changes in the organization of water within a binding pocket influence the thermodynamics of protein-ligand association (36)…”
mentioning
confidence: 99%